Experimental Study on Shear Resistance of Rubber Concrete Brick Masonry. Issue 1 (February 2020) - Wang, Fengchi; Chong, Bowen; Ding, Junsheng
Abstract: In this paper, the shear properties of two kinds of brick masonry specimens are studied, including rubber concrete brick masonry (RBM) and common fired brick masonry (CBM). The specimen is a double shear specimen composed of three layers of nine bricks, with the size of 179 mm × 240 mm × 365 mm. Through the shear strength test, the failure forms of masonry are obtained, and the failure types are classified. According to the experimental data, the shear strength of RBM and CBM are compared, and the factors that affect the shear strength are analyzed. The influence of mortar on the shear strength of rubber concrete brick masonry is obtained. Through regression analysis, the recommended equation of RBM shear strength average value, RBM shear strength standard value and RBM shear strength design value are obtained.